2012
DOI: 10.1002/acr.21716
|View full text |Cite
|
Sign up to set email alerts
|

Association of C‐reactive protein with high disease activity in systemic sclerosis: Results from the Canadian Scleroderma Research Group

Abstract: Objective. This study was performed to determine the prevalence of elevated C-reactive protein (CRP) levels and the significance of CRP in clinical parameters in systemic sclerosis (SSc; scleroderma) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
73
5
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 46 publications
13
73
5
5
Order By: Relevance
“…In support of this is the trend whereby the baseline median CRP was higher in ILD participants who deceased (9.2 mg/l vs 6.0 mg/l; p=0.066), and a higher proportion of participants in the deceased group had a CRP>8 mg/l (66.7% versus 33.3%; p=0.065). This is in keeping with findings where CRP>8mg/l was associated with mortality in SSc ILD patients (53,54) .…”
Section: Interstitial Lung Disease Survival In Systemic Sclerosissupporting
confidence: 91%
See 1 more Smart Citation
“…In support of this is the trend whereby the baseline median CRP was higher in ILD participants who deceased (9.2 mg/l vs 6.0 mg/l; p=0.066), and a higher proportion of participants in the deceased group had a CRP>8 mg/l (66.7% versus 33.3%; p=0.065). This is in keeping with findings where CRP>8mg/l was associated with mortality in SSc ILD patients (53,54) .…”
Section: Interstitial Lung Disease Survival In Systemic Sclerosissupporting
confidence: 91%
“…Muangchan and colleagues (2012) (53) demonstrated that a baseline C-reactive protein (CRP) > 8 mg/litre was associated with "disease activity, severity, poor pulmonary function, and shorter survival." This was supported by Liu et al (2013) (54) who found that baseline CRP predicted progression in FVC decline, and is associated with shorter survival.…”
Section: Interstitial Lung Disease Severity and Progression In Systemmentioning
confidence: 99%
“…In order to better understand the relationship between disease duration and changes in expression of investigated molecules, patients were divided into those with short- and long-term disease. In agreement with previous studies, patients were considered as having short-term disease if disease duration was not longer than 3 years in dSSc or 5 years in lSSc measured from the first non-Raynaud symptom [29-31]. Accordingly, patients with dSSc in whom disease lasted longer than 3 years and patients with lSSc in whom disease lasted longer than 5 years were considered as having long-term disease.…”
Section: Methodsmentioning
confidence: 64%
“…Systemic inflammation is present in SSc at low grade [10] and increased serum levels of eosinophilic major basic protein have been described in early SSc [11]. We hypothesized therefore that eosinophils are activated in peripheral circulation facilitating their recruitment to the lung and that this is reflected in differentially expressed activation markers.…”
Section: Introductionmentioning
confidence: 96%